A Computer Program for Dynamic Multipliers - Liew, C. K. (Econometrica, 1973)
THE DYMULT (dynamic multipliers) program is designed to calculate impact, interim, and total multipliers of a simple linear simultaneous equations model with lags. Builders of an aggregate econometric model have often concentrated on the validity of signs and magnitudes of the estimated regression coefficients of each structural equation and neglected to check the stability conditions of the system, which could be a symptom of specification errors in the model. The DYMULT program checks the stability conditions of the system of equations and calculates the impact, interim, and total multipliers. The matrix form of a simple lag linear simultaneous equations model can be written as follows: